Practice theory in action : empirical studies of interaction in innovation and entrepreneurship - Campbell, Betsy, 1966- (Abingdon, Oxon ; New York, NY : Routledge, 2019)
This book explores intra-team interaction in workplace settings devoted to technological breakthroughs and innovative entrepreneurship. The first set of studies to investigate these economically important institutions through the lens of talk-at-work, this book begins by discussing the ethnomethodological traditions of Conversation Analysis and institutional interaction and linking them to innovation and entrepreneurship. The book offers rich and detailed empirical accounts of teams talking new technologies and new ventures into being. By focusing on the observable language of teams in action, the book reveals the situated practices that teams use to enact their work, including the means by which team members verbally grapple with the uncertainties inherent in doing work in uncharted domains. The book presents important findings about the conversational accomplishment of work and demonstrates the value of examining the practices of teams in action. A valuable contribution to studies of talk-in-interaction, as well as entrepreneurship-as-practice, this book can help to bridge the gap between scholarly investigations and the practical experiences of entrepreneurs. The author closes by considering the ways that practice-based studies of entrepreneurial work can improve issues of diversity and inclusion within the entrepreneurial ecosystem. This book is intended to serve as an invaluable sourcebook for scholars and students interested in innovation, entrepreneurship, and organizations as well as those focused on applied Conversation Analysis. The book's insights are presented in a richly detailed manner while remaining accessible to readers who are new to the methodologies and activity contexts.
Part IV Looking through other lenses9 Resilience as verbal practice; 10 Bricolage as verbal practice; Part V Advancing theory and practice; 11 Entrepreneurial uncertainty is a members' issue; 12 Teaching the conversational competencies of innovation work; Afterword on the democratization of innovation; Appendix: Transcription conventions; Index
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Creative ability in business; New products; Technological innovations -- Management; Organizational behavior; Entrepreneurship; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Entrepreneurship